Biological aspects and mating behavior of Leucothyreus albopilosus (Coleoptera: Scarabaeidae) - Kleyton Rezende Ferreira (Revista de Biología Tropical, 2016)
The genus Leucothyreus has been linked to some commercial plant crop pests. Eventhough several species have been described for this genus, information about this group is still scarce. This study investigated some biological aspects and mating behavior in Leucothyreus albopilosus. Studies were conducted at the State University of Mato Grosso do Sul, in the municipalities of Aquidauana and Cassilândia, MS, Brazil. For biological studies, adults were collected with light traps from February 2011 to February 2012, and for behavior analyses from September to December 2014. Biological studies were undertaken every three days and included the eggs inspection, and the separation of the newly hatched larvae to observe and describe their developmental stages; to monitor larval growth and differentiate larval instars, we measured the larvae cephalic capsule. Life cycle was determined starting from the newly laid eggs until adult death. For mating behavior studies, adults obtained with light traps were taken to the laboratory. As soon as they started flying in the evening, couples were formed and copulation steps were recorded. In the field, we observed that adults were mostly collected during warmer and wetter periods (from August to March). Our results showed that the embryonic period of L. albopilosus lasted 20.5 days, the 1st, 2nd and 3rd instars lasted 31.0, 33.1 and 85.6 days, respectively. The pupal stage lasted 20 days, and the egg to adult period was completed in 185.5 days; these results suggest that L. albopilosus can be characterized as a univoltine species. Observations of mating behavior in the laboratory showed that, after the sunset, adults projected a small portion of clypeus near the soil surface and flew off seeking a female to mate. The female could accept or reject the male for mating. When the female accepted the male, copulation occurred from 19:00 to 23:00 hours, and lasted 19.45 minutes on average. Sometimes females refused to mate, probably because the male or female were not sexually mature to perform copulation, and there might be a chemical communication between the adults. Adults were observed feeding on ripe bananas (Musa sp., Musaceae) and on mangaba flowers (Hancornia speciosa, Apocynaceae) in the laboratory. With this work we contributed with the description of mating behavior in the genus Leucothyreus and concluded that the biological cycle was completed in less than 200 days.